2015
DOI: 10.1093/jnci/dju397
|View full text |Cite
|
Sign up to set email alerts
|

The Contributions of Breast Density and Common Genetic Variation to Breast Cancer Risk

Abstract: We evaluated whether a 76-locus polygenic risk score (PRS) and Breast Imaging Reporting and Data System (BI-RADS) breast density were independent risk factors within three studies (1643 case patients, 2397 control patients) using logistic regression models. We incorporated the PRS odds ratio (OR) into the Breast Cancer Surveillance Consortium (BCSC) risk-prediction model while accounting for its attributable risk and compared five-year absolute risk predictions between models using area under the curve (AUC) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
155
3
16

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 176 publications
(183 citation statements)
references
References 40 publications
9
155
3
16
Order By: Relevance
“…However, comparison with the few studies to date on the PRS and breast cancer association [21, 22] suggests that there is some attenuation of the association in the SERM-treated population. Although the PRS distributions are not directly comparable across these studies, a one-unit increase in PRS was associated with a 1.4-fold increased risk of breast cancer in this NSABP population, but associated with a 1.8-fold increase (95 % CI 1.6–2.1) in a general population [21]. Because of the known risk reduction associated with these SERMs, the SNPs (PRS) may not be as strong a risk factor in moderate to high-risk women on tamoxifen and raloxifene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, comparison with the few studies to date on the PRS and breast cancer association [21, 22] suggests that there is some attenuation of the association in the SERM-treated population. Although the PRS distributions are not directly comparable across these studies, a one-unit increase in PRS was associated with a 1.4-fold increased risk of breast cancer in this NSABP population, but associated with a 1.8-fold increase (95 % CI 1.6–2.1) in a general population [21]. Because of the known risk reduction associated with these SERMs, the SNPs (PRS) may not be as strong a risk factor in moderate to high-risk women on tamoxifen and raloxifene.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these validated loci are estimated to explain up to 14 % of familial breast cancer risk [5]. Two recent studies showed that a polygenic risk score (PRS) composed of 76–77 of these genetic loci can identify individuals at increased breast cancer risk in the general population [21, 22]. Specifically, those at highest risk by the PRS had a 1.8-fold increased risk for breast cancer relative to the second quartile of PRS, and those in the lowest quartile had a reduced risk (0.6 fold) of breast cancer [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boyd (2013) described 10 epidemiological studies in which breast density was demonstrated to be related to the risk of breast cancer, the results of which demonstrate the usefulness of this method. Two recent studies have confirmed that per cent mammographic density is the strongest risk factor for breast cancer besides genetic variants and family history (Vachon et al, 2015;Maskarinec et al, 2015). In several interventional studies increased mammographic density has been shown to be related to the intervention if the intervention was a combined hormonal replacement therapy in postmenopausal women (reviewed in Ursin and Qureshi, 2009).…”
Section: Endpoint: Mammographic Densitymentioning
confidence: 95%
“…Breast cancer screening and early cancer detection programs include breast self-examination [7,8,9], clinical breast examination (CBE) [10,11,12,13,14,15,16,17,18,19], mammography [14,15,16,19,20,21,22,23,24], ultrasonography [14,23,24,25,26], and magnetic resonance imaging [23,27]. Although there has been constant progress in the understanding of risk factors and genetic dispositions for breast cancer [28,29,30,31,32,33,34,35,36], the majority of breast cancer cases still occur without known predictors. This study is concerned with the introduction of vision-impaired medical tactile examiners (MTEs) for performing CBE in a diagnostic breast unit in order to assess the feasibility, acceptance, and diagnostic value of this approach.…”
Section: Introductionmentioning
confidence: 99%